Cataract surgery: factors influencing decision to treat and implications for training (south-east Scotland 2008–2014) - Sniatecki, Jan J (Clin Ophthalmol, 2015)
PURPOSE: To describe the population referred for cataract surgery, identify factors that influenced decision to treat, and patients suitable for ophthalmic training. PATIENTS AND METHODS: A total of 2,693 consecutive referrals over 6 years were interrogated using Business Objects software on cataract electronic patient records. RESULTS: A total of 2,693 patients were referred for cataract surgery (group A). Of these patients 2,132 (79%) had surgery (group B) and 561 (21%) did not (group C). Age for group B vs group C: 672 (32%) vs 115 (20%) ≤69 years, P<0.001; 803 (38%) vs 225 (40%) 70–79 years, P=0.48; 586 (27%) vs 203 (36%) 80–89 years, P<0.05; 71 (3%) vs 18 (3%) ≥90 years, P=1.0. Visual acuity, group B vs group C: 556 (26%) vs 664 (59%) 6/12 or better; 1,275 (60%) vs 367 (33%) 6/18–6/60; 266 (12%) vs 64 (6%) counting fingers or worse, P<0.05. Medical history for group B vs C: cognitive impairment: 55 (2.6%) vs 29 (5.2%), P<0.05; cardiovascular accident: 158 (7.4%) vs 60 (10.7%), P<0.05; diabetes: 372 (17.4%) vs 96 (17.1%), P=0.87; COPD/asthma: 382 (17.9%) vs 93 (16.6%), P=0.53; heart disease: 535 (25.1%) vs 155 (27.6%), P=0.35; hypertension: 971 (45.5%) vs 263 (46.9%), P=0.73. Ocular history for group B vs C was significant (P<0.05) for age-related macular degeneration 255 (12.0%) vs 93 (16.6%), other macular pathology 38 (1.8%) vs 25 (4.5%), corneal pathology 92 (4.3%) vs 36 (6.4%), amblyopia 37 (1.7%) vs 22 (3.9%). Detailed data on presenting complaint, ophthalmic history, and social status is discussed. CONCLUSION: We observed that surgery at a younger age with good levels of visual acuity was a factor in deferring cataract surgery. Cognitive impairment, cardiovascular accident, amblyopia, corneal and macular pathology significantly affected decision not to operate. We estimate that 80% of patients would be suitable for ophthalmic training.